Implikasi Penggunaan Media Sosial Terhadap Produktiviti Sumber Manusia Di Institut Pengajian Tinggi Awam Malaysia - Izharrudin, Siti Zakiah (2018)
There has been a widespread usage of social media facilited by the Internet-based technology and its usage has become ubiquitious even at the workplace. However, the impacts of using social media at the workplace have received conflicting views as some argue that while it enhances organizational productivity, it leads to negative work-related behaviours. Although there have been extensive studies on the use of social media among students and employees at private sectors, studies of the use of social media among employees in higher learning education are still lacking. This study aims to investigate the implications of social media usage aspects among human resources at universities, focusing on the relationship and the affect of the aspects of social media use toward the productivity of employees as well as the perceptions impacts of using social media at two Malaysian universities. This study employed a quantitative survey research method that took place at two universities of Malaysian Technical Universities, namely Universiti Teknikal Malaysia Melaka and Universiti Malaysia Pahang. Questionnaires were distributed to a total of 370 respondents comprising of academic management staff, nonacademic management staff, academic staff and administrators. The data were analyzed using Statistical Package for Social Science (SPSS) version 22.0.The results show that the highest social media usage is the usage of WhatsApp and Google via smartphone. Further, the time spent for personal usage is less than for work purposes. Employees tend to use social media for communication, such as sending and receiving email, communicating formally and giving alerts and reminders to colleagues, subordinates and students. There is a positive relationship between the aspects of social media use and the level of productivity at the organization. The types and purposes of social media use demonstrate positive relationships with human resource productivity levels, while the medium and the frequency of usage do not show any significant relationship with the level of human resource productivity. Based on the multiple regression, it is found that the aspect of social media use (types and purposes) has affectes human resource productivity which is about 6.2 percent. The value of F ANOVA is greater than f table which is not equal than zero. It shows that the aspect of social media usage has significantly affected the human resource productivity. Based on the perception of individual, majority agreed that the social media use has brought more positive impact toward individual staff compared to organizational. There is a relationship between the effects of social media usage and individual productivity. No relationship was found between the effects of social media usage and organizational productivity. It can be concluded that the use of social media gives positive impacts to job productivity of human resources, at institutes of higher education. However, it is suggested that appropriate monitoring system should be considered to ensure that employees do not deviate from using the social media for personal purposes. This study also contributes to the development of a model on the use of social media at the workplace among employees based derived from UGT.